O Supremo Tribunal Federal como agente tecnocrático no exercício da jurisdição constitucional na solução de casos complexos : análise das ações diretas de inconstitucionalidade nº 3937/SP e nº 3357/RS - Faria, Maristela Medina (2016)
Many changes have taken place in contemporary society causing impacts in its different sectors, making it much more complex and insecure than in past times. The alteration on the decision-making system of the Brazilian society is among the main changes today. The post-modern context contributed to the occurrence of the transfer of state power of the Legislative and Executive Powers to the Judiciary Power, specifically to the Federal Court of Justice, leading to an expansion on the actuation range of this institution mainly through the exercise of the constitutional jurisdiction. This has caused a crisis of legitimacy in society once the Court will now decide the political and social fundamental issues. In this scenario, the Direct Action of Unconstitutionality n° 3937/SP and n° 3357/RS are highlighted and both are being tried by the Supreme Court. Such emphasis is given, since it is a matter of high complexity and social repercussion that will be decided by a legal institution and not a political one. Thus, this work aims to analyze the role of the Supreme Court in the context of contemporary society on the trial of complex and controversial cases, particularly on the trial of Direct Action of Unconstitutionality n° 3937/SP and n° 3357/RS. This study has noticed that due to the post-modern context the majority of the Supreme Court Ministers tend to base their votes in constitutional principles and no longer limit themselves to a formal review of the constitutionality of laws, which indicates a substantialist approach. Moreover, it can be noticed the deliberative potential of the Court as well as the influence of the post-modern features, such as risk, uncertainty and insecurity on the elaboration of the Minister‟s votes. Therefore, sometimes, such as the case in study, the Supreme Court has acted as a technocratic agent in Brazilian society once fundamental political and social decisions for society especially when it comes to complex and controversial cases are being taken by the Supreme Court, which is composed by “Law technicians” and such decisions are mainly based in technical data and scientific studies. For the accomplishment of this work, it has been adopted the inductive approach and monographic procedure method and the bibliographical and documentary research technique.